Polymer pen lithography-fabricated DNA arrays for highly sensitive and selective detection of unamplified Ganoderma boninense DNA - Rani, Ekta; Mohshim, Siti Akhtar; Ahmad, Muhammad Zamharir; Goodacre, Royston; Alang Ahmad, Shahrul Ainliah; Wong, Lu Shin (MDPI, 2019)
There is an increasing demand for lithography methods to enable the fabrication of diagnostic devices for the biomedical and agri-food sectors. In this regard, scanning probe lithography methods have emerged as a possible approach for this purpose, as they are not only convenient, robust and accessible, but also enable the deposition of “soft” materials such as complex organic molecules and biomolecules. In this report, the use of polymer pen lithography for the fabrication of DNA oligonucleotide arrays is described, together with the application of the arrays for the sensitive and selective detection of Ganoderma boninense, a fungal pathogen of the oil palm. When used in a sandwich assay format with DNA-conjugated gold nanoparticles, this system is able to generate a visually observable result in the presence of the target DNA. This assay is able to detect as little as 30 ng of Ganoderma-derived DNA without any pre-amplification and without the need for specialist laboratory equipment or training.